Archimedes screw turbine model simulation on the effect of external and internal design parameters in power generation - Nurul Suraya, Azahari (2022)
Year after year, electricity demand increases due to the world's rapid growth, which uses electricity as its main source of energy. In order to overcome the challenge of generating electricity from conventional energy resources that contribute to the greenhouse effect, renewable energy is in demand. One of the alternatives to generating electricity in a clean environment is the Archimedes screw turbine (AST). The objective of this research study is to investigate the AST slope inclination angle, diameter ratio, and number of bladed screws based on previous design concepts for power generation and determine the power output and highest efficiency based on the internal and external parameters. This research is aimed at studying the AST design concept for generating electricity. The design concept was analysed based on the geometric parameters, which were then validated between the simulation and actual data. Three parameters considered in this research were the slope inclination angle, α ratio of diameter, Dr and number of bladed screws, N. Each parameter affects the AST power generation significantly. The simulation of the AST design concept was carried out using ANSYS CFX. The simulation was divided into several steps, such as validation between the simulation and experimental data, and simulation of the AST using three different parameters at a constant flow rate and rotational speed. A total of 36 simulations were run based on constant flow rate with a number of bladed screws of 1,2 and 3, with a diameter ratio of 0.25,0.5 and 0.6 combined with a slope inclination angle of 20°, 25°,35° and 40°. From the simulation, the highest power of 2.3W was produced at 1 bladed screw, 0.5Dr and 40°, whereas the highest efficiency (79.42%) occurred at 3 bladed screws, 20° and 0.25Dr. Each of the designs of the parameter studies impacted the power production and efficiency of AST.